METODOLOGI PEMAHAMAN HADIS PERSPEKTIF YUSUF QARDAWI TENTANG HADIS KEWARISAN BEDA AGAMA - A. Fauzi Aziz; Wahidul Anam (Lembaga Penerbitan Jurnal Ilmiah Institut Agama Islam Bani Fattah Jombang, 2023)
There should be no ambiguity regarding how Islamic law interprets the concept of inheritance. This is so because both the Qur'an and the Sunnah provide comprehensive justifications for the inheritance law. With Hadyu al-Islam Fatwa Mu